Evaluating Spatial Hearing Using a Dual-Task Approach in a Virtual-Acoustics Environment - Salorio-Corbetto, Marina; Williges, Ben; Lamping, Wiebke; Picinali, Lorenzo; Vickers, Deborah (Frontiers in Neuroscience, 2022)
Spatial hearing is critical for communication in everyday sound-rich environments. It is important to gain an understanding of how well users of bilateral hearing devices function in these conditions. The purpose of this work was to evaluate a Virtual Acoustics (VA) version of the Spatial Speech in Noise (SSiN) test, the SSiN-VA. This implementation uses relatively inexpensive equipment and can be performed outside the clinic, allowing for regular monitoring of spatial hearing performance. The SSiN-VA simultaneously assesses speech discrimination and relative localisation with changing source locations in the presence of noise. The use of simultaneous tasks increases the cognitive load to better represent the difficulties faced by listeners in noisy real-world environments. Current clinical assessments may require costly equipment which has a large footprint. Consequently, spatial hearing assessments may not be conducted at all. Additionally, as patients take greater control of their healthcare outcomes and a greater number of clinical appointments are conducted remotely, outcome measures that allow patients to carry out assessments at home are becoming more relevant. The SSiN-VA was implemented using the 3D Tune-In Toolkit, simulating seven loudspeaker locations spaced at 30° intervals with azimuths between –90° and +90°, and rendered for headphone playback using the binaural spatialisation technique. Twelve normal-hearing participants were assessed to evaluate if SSiN-VA produced patterns of responses for relative localisation and speech discrimination as a function of azimuth similar to those previously obtained using loudspeaker arrays. Additionally, the effect of the signal-to-noise ratio (SNR), the direction of the shift from target to reference, and the target phonetic contrast on performance were investigated. SSiN-VA led to similar patterns of performance as a function of spatial location compared to loudspeaker setups for both relative localisation and speech discrimination. Performance for relative localisation was significantly better at the highest SNR than at the lowest SNR tested, and a target shift to the right was associated with an increased likelihood of a correct response. For word discrimination, there was an interaction between SNR and word group. Overall, these outcomes support the use of virtual audio for speech discrimination and relative localisation testing in noise.